Analisis Pola Komunikasi Scientific pada Pembelajaran Biologi SMA - Itsnaini, Susana Mega; Muzzazinah, Muzzazinah; Ramli, Murni; Yulianto, Yulianto; Setyorini, Anik (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2017)
This research aims to study (1) the pattern of scientific communication in biology classes, and (2) the factors and reasons hinder the communication process during the learning process. This is a classroom observation conducted in two classes of grade XI Science of Gondangrejo High School, which were selected randomly. Fifty-five students participated, and two biology teachers had also been involved. The pattern of scientific communication was analyzed based on 10 times observations of both classes, then all communications recorded and analyzed based on VICS Flanders. The hindrances of communication were checked based on categorization introduced by Lunenburg, which consists of four: process, physics, semantic, and psycho social. The findings of the research shows that the pattern of communication is mostly balance between teacher and students, which is represented by region C G J K L M P R (52.43%). Whilst, the area of teacher's domination is 24.79% (A B D E F H I ), and the area of student’s domination scores 22.78% (N O S T). The pattern of scientific communication is two ways communication between teacher and students, but the frequency of student to initiate the communication remains low. The factors hinder the communication process are process barriers.